Rural voices : 15 authors challenge assumptions about small-town America - Carpenter, Nora; Roe, Monica M., 1978-; Costello, Rob; Bowles, David (David O.); Bybee, Veeda; Bybee, Veeda; Cosby, S. A.; Perez, Ashley Hope; Mendez, Yamile Saied; Price, Tirzah; Gill, David Macinnis, 1963-; Hopson, Nasugraq Rainey; et al. (Candlewick Press, 2020)
"For most of America's history, rural people and culture have been casually mocked, stereotyped, and, in general, deeply misunderstood. Now an array of short stories, poetry, graphic short stories, and personal essays, along with anecdotes from the authors' real lives, dives deep into the complexity and diversity of rural America and the people who call it home. Fifteen extraordinary authors--diverse in ethnic background, sexual orientation, geographic location, and socioeconomic status--explore the challenges, beauty, and nuances of growing up in rural America. From a mountain town in New Mexico to the gorges of New York to the arctic tundra of Alaska, you'll find yourself visiting parts of this country you might not know existed--and meet characters whose lives might be surprisingly similar to your own."--Amazon.